2001
DOI: 10.1089/152460901750067124
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable and Nonmodifiable Factors Associated with Osteoporosis in Postmenopausal Women: Results from the Third National Health and Nutrition Examination Survey, 1988–1994

Abstract: We wished to study the relationship between modifiable and nonmodifiable factors that were correlated with osteoporosis using a national sample of women aged 50 years and older who have never been on hormone replacement therapy (HRT). We used a cross-sectional study design with a nationally representative sample with a detailed clinical examination and a home interview. Between 1988 and 1994, 1953 postmenopausal women who had never been on HRT, aged 50 years and older, were examined as part of the Third Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 20 publications
4
27
0
2
Order By: Relevance
“…15 Thus, insufficient knowledge regarding osteoporosis makes women assume that the symptoms were simply a part of the normal aging process. In all cited cases, the obtained scores indicated that knowledge about osteoporosis is poor or limited among surveyed subjects so health educational programs and health services regarding osteoporosis are necessary for women living in Qatar.…”
Section: Knowledge About Osteoporosismentioning
confidence: 99%
“…15 Thus, insufficient knowledge regarding osteoporosis makes women assume that the symptoms were simply a part of the normal aging process. In all cited cases, the obtained scores indicated that knowledge about osteoporosis is poor or limited among surveyed subjects so health educational programs and health services regarding osteoporosis are necessary for women living in Qatar.…”
Section: Knowledge About Osteoporosismentioning
confidence: 99%
“…As the prevalence of osteoporosis and associated fractures differ from country to country, a lot of factors except menopause may be liable for the conflicting incidence. For primary postmenopausal osteoporosis, the non-modifiable risk factors are female sex, hormonal changes, family history of osteoporosis, early menopause and older age while amendable factors include low calcium intake, alcohol, modest physical activity, smoking and lower body weight (Snelling et al, 2001). Nutrition is vital for bone health.…”
Section: Introductionmentioning
confidence: 99%
“…For example, vitamin D and bisphosphonates have been shown to reduce fractures and falls [6][7][8], and funding drugs to seniors may be more cost-effective than spending future health care dollars on fracture care and institutionalization [9].…”
Section: Introductionmentioning
confidence: 99%